EFFECT OF THICKNESS AND ANNEALING TEMPERATURE ON D.C. ELECTRICAL CONDUCTIVITY OF GaAs FILMS AND (C-V) CHARACTERIZATION OF GaAs/Ge HETEROJUNCTION - Hasan, Nahida B.; Alias, Maysoon F.; Al-Haddad, Raad M.; Hasan, Huda B. (European Scientific Journal, ESJ, 2014)
GaAs films with different thickness (0.4, 0.7, 1.0 and 1.5) μm have been prepared by thermal flash evaporation technique on glass substrate and Ge wafer at substrate temperature equal to 433K under vacuum of 10-5 mbar with rate of deposition equal to 0.015 μm/min. These films have been annealed at different annealing temperatures (473 and 523) K. The d.c. conductivity for all deposited films increases with thickness increases, and decreases with increase of annealing temperatures. The electrical activation energies (Ea1) decrease with increasing of thickness and increase with increasing of annealing temperatures. Also GaAs/Ge heterojunction has been prepared at different thickness and annealing temperatures. The reverse bias capacitance was measured as a function of bias voltage at frequency 1 MHz, and it is indicated that these heterojunction are abrupt. The capacitance decreases with increasing the reverse bias voltage, also with increasing of thickness and annealing temperatures. The width of depletion layer increases with increase of the thickness and annealing temperatures respectively. The value of built–in voltage varies between (0.56–1.08) Volt when thickness changes from 0.4 to 1.5μm.